Viability of Anisakis spp. Larvae After Direct Exposure to Different Processing Media and Non-Thermal Processing in Anchovy Fillets - Vida Šimat; Željka Trumbić (Fishes, 2019)
Anisakiasis is fish-borne zoonoses caused by nematodes of the genus Anisakis, contracted by the ingestion of live L3 infective larvae through consumption of raw, undercooked or thermally unprocessed seafood products, such as carpaccio, and white marinated and dry-salted anchovies. In order to maintain the organoleptic properties of the product, the freezing of fish prior to processing is often ignored, especially in households, and traditional processing methods are not sufficient to kill Anisakis larvae. In this study, we investigated the survival and resistance of Anisakis spp. larvae in different processing solutions including varying salt and sugar content, lemon juice, acetic acid, alcohol, wine, and apple vinegar. We also performed a viability test of larvae during processing in anchovy fillets. When exposed directly to different NaCl concentrations, larvae were killed after approximately three days in the strongest (35%) and 10 days in the weakest solution (5%). In lemon juice and lemon juice with added acetic acid, the survival of larvae was around 5 days. In intact alcohol vinegar, larvae were killed under less than 48 h, while in the solution with water their resistance was prolonged to almost 40 days. In fillets, larvae showed increased resistance during carpaccio and white wine vinegar marinades and only dry salting was effective in destroying Anisakis spp. larvae.